2019
DOI: 10.1093/bioinformatics/btz029
|View full text |Cite
|
Sign up to set email alerts
|

AllerCatPro—prediction of protein allergenicity potential from the protein sequence

Abstract: Motivation Due to the risk of inducing an immediate Type I (IgE-mediated) allergic response, proteins intended for use in consumer products must be investigated for their allergenic potential before introduction into the marketplace. The FAO/WHO guidelines for computational assessment of allergenic potential of proteins based on short peptide hits and linear sequence window identity thresholds misclassify many proteins as allergens. Results … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
98
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 129 publications
(98 citation statements)
references
References 42 publications
0
98
0
Order By: Relevance
“…Global population HLA allele coverage for this peptide subset was separately calculated for class I and class II molecules using the Population Coverage tool from IEDB 52 and the predicted HLA alleles identified in our analyses. The potential toxicity and allergenicity of each peptide were calculated using the ToxinPred 53 and AllerCatPro 54 web tools, respectively. Default parameters were used for all sequence inputs.…”
Section: Prediction Of Sars-cov-2 T Cell Epitopes Prediction Of Hla mentioning
confidence: 99%
“…Global population HLA allele coverage for this peptide subset was separately calculated for class I and class II molecules using the Population Coverage tool from IEDB 52 and the predicted HLA alleles identified in our analyses. The potential toxicity and allergenicity of each peptide were calculated using the ToxinPred 53 and AllerCatPro 54 web tools, respectively. Default parameters were used for all sequence inputs.…”
Section: Prediction Of Sars-cov-2 T Cell Epitopes Prediction Of Hla mentioning
confidence: 99%
“…The selected T-cell epitopes were predicted for allergenicity by using the AllerCatPro server [31] and toxicity prediction using a toxpred tool.…”
Section: Non-allegenicity and Non-toxicity Prediction Of Selected T Cmentioning
confidence: 99%
“…To predict the peptides' allergicity, the AllergenFP v.1.0 [22] and AllerCatPro v. 1.7 [23] servers were used. In contrast, to predict the peptides' toxicity, the ToxinPred server [24] was used.…”
Section: Allergicity and Toxicity Predictionmentioning
confidence: 99%
“…Besides the binding with the MHC molecules, the predicted peptide must be non-toxic and non-allergen, hence, their safety was predicted using the AllergenFP v.1.0 [22], AllerCatPro [23] v. 1.7, ToxinPred [24] servers. The result showed that all the peptides were non-toxic.…”
Section: Thementioning
confidence: 99%
See 1 more Smart Citation